Ten essential skills for electrical engineers - Dorr, Barry L., 1958- (Wiley, 2014)
"Engineers know that, as in any other discipline, getting a good job requires practical, up-to-date skills. An engineering degree provides a broad set of fundamentals. Ten Essential Skills applies those fundamentals to practical tasks required by employers. Written in a user-friendly, no-nonsense format, the book reviews practical skills using the latest tools and techniques, and features a companion website with interview practice problems and advanced material for readers wishing to pursue additional skills. With this book, aspiring and current engineers may approach job interviews confident in their grasp of the engineering skills that their employers seek."--